Flavonoid diversity in bitter and debittered seeds of Andean lupin (Lupinus mutabilis Sweet) - Tian, Ye; Cortés-Avendaño, Paola; Yang, Baoru; Glorio-Paulet, Patricia; Repo-Carrasco-Valencia, Ritva; Suomela, Jukka-Pekka (Elsevier BV, 2025)
Seeds of ten Andean lupin (Lupinus mutabilis Sweet) ecotypes were collected from different regions of Peru and treated with an aqueous debittering method. Both untreated and treated seeds were analyzed by using LC-MS to investigate flavonoid profiles of different ecotypes and impact of debittering process on these compounds. Thirteen isoflavones (mainly as glycosides of genistein and methoxy-genistein) and eight flavones (glycosylated apigenins and methyl-luteolins) were characterized as the main flavonoids in the seed samples. The untreated lupin seeds contained 187–252 mg/100 g (dry weight) of flavonoids. The main difference among lupin ecotypes was observed in the levels of genistein-malonylhexoside, methoxy-genistein-malonylhexoside, and methyl-luteolin-malonylhexoside. After the debittering treatment, the total flavonoid content in the seeds was decreased to 125–203 mg/100 g dry weight, the aglycones of genistein, methoxy-genistein, and methyl-luteolin being the key distinguishing compounds of ecotypes. The aqueous treatment was effective in degrading flavonoid glycosides and releasing the corresponding aglycones.